Thermo-dynamic irreversibility induced by natural convection in square enclosure with inner cylinder. Part-II: Effect of vertical position of inner cylinder. (June 2016) - Doo, Jeong Hoon; Mun, Gi Su; Ha, Man Yeong; Seong, Seon Yoo
Highlight: The immersed boundary method was used, based on the finite volume method. Abstract: Two-dimensional numerical simulations were conducted to investigate the natural convection heat transfer induced by the temperature difference between cold walls of the square enclosure and a hot inner circular cylinder in the Prandtl number range of 10 −2  ⩽  Pr  ⩽ 10 2 and Rayleigh number range of 10 3  ⩽  Ra  ⩽ 10 6 . In this paper as a sequent research of Mun et al. (2015), the additional geometrical configuration of the system, which is the variation in the vertical position of the inner cylinder, was considered. The change in the structure of convection cells and corresponding heat transfer characteristics were analyzed, which are induced by the variation in the vertical position of the inner cylinder located in the enclosure. And the characteristics of the entropy generation due to heat transfer and fluid friction associated with the flow and thermal structures were addressed in this study.